Albumseite 54
Wirtschaft;Industrie;verschiedene Industriezweige;Musikinstrument soziale Fragen;sozialer Schutz;Sozialpolitik;Kinderbetreuung politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Jugendbewegung